2012
DOI: 10.4038/jnsfsr.v40i1.4167
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and toxicological activities of some depsides and depsidones

Abstract: Boustie & Grube, 2005). Depsides and depsidones are the most common secondary products uniquely produced in lichens by the fungal symbiont, amounting to as large as 5-10% of thallus' dry weight. The core structural motif of this acetyl polymalonylderived family of about 700 depsides and depsidones is uniform across thousands of lichen species and generally consists of two phenolic rings with various substituents, joined by ester and/or ether linkages. Depsides and depsidones have manifold properties, such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 10 publications
1
40
1
1
Order By: Relevance
“…Manojlović et al [5] reported about the antimicrobial activity of salazinic and protocetraric acids. Also, strong antimicrobial activity was found for atranorin [18,19].…”
Section: Discussionmentioning
confidence: 89%
“…Manojlović et al [5] reported about the antimicrobial activity of salazinic and protocetraric acids. Also, strong antimicrobial activity was found for atranorin [18,19].…”
Section: Discussionmentioning
confidence: 89%
“…lecanoric acid and orsellinic acid were present in P. tinctorum while salazinic acid and con-salazinic acid were present in P. cristiferum. It is shown from earlier studies that lichen metabolites such as atranorin (Goel et al, 2011), lecanoric acid (Thadhani et al, 2012), salazinic acid (Candan et al, 2007;Goel et al, 2011) exhibit antimicrobial activity. In the present study, the observed antifungal potential of P. tinctorum and P. cristiferum to inhibit seed-borne fungi could be ascribed to the presence of these metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Among the metabolites, depsides and depsidones are most common. Studies have shown that extracts and purified metabolites from lichens exhibit diverse biological activities Molnár and Farkas, 2010;Goel et al, 2011;Thadhani et al, 2012;Shrestha and St. Clair, 2013;Babiah et al, 2014). Parmotrema A. Massal.…”
Section: Introductionmentioning
confidence: 99%
“…Methanolyis of lecanoric acid isolated from Cladonia sp., H. obscurata and P. grayana, has yielded the mononuclear aromatic compound methyl orsellinate ( Figure 16), which exhibited a moderate antibacterial activity against E. coli, B. subtillus and S. typhi (Thadani et al, 2012). ( Figure 19), isolated from the stem bark of Garcinia mangostana L., has been found to be active against vancomycin resistant Enterococci (VRE) and methicillin resistant Staphylococcus aureus (MRSA) with MIC values of 6.25 and 6.25 to 12.5 µg/mL, respectively.…”
Section: Antibacterial Activitymentioning
confidence: 99%